Media Portrayal of Female Singers Reflected from Radio Interviews - Radha Andhra Swari; Made Sani Damayanthi Muliawan (Sean Institute, 2024)
Media has the power to influence the way people perceive things, as of why, there is the term “media portrayal”. Prior works have attempted to investigate on media portrayal, particularly how women are depicted in the media. Hence, this study examined the media portrayal of female singers in Elvis Duran and The Morning Show. Descriptive qualitative method was applied in this study. The data was gathered from Elvis Duran and The Morning Show’s official YouTube channel, and three interviews with different female singers were chosen. The analysis was conducted using a critical discourse analysis approach, namely Three Dimensional Approach. In addition to that, this study focuses on the lexical choices used by the radio hosts when interviewing the female singers. The findings were further analyzed by referring to gender-related theories. Based on the results, it is evident that there are certain words that are oftentimes associated with female singers, some of which are “feeling”, “relationships”, and “breakup song”. These portrayals of female singers support genderlect theories that women tend to use language to express their feelings and build intimate relationships with others.